Neuroimmune activation in arthritic and neuropathic low back pain : implications for interventional therapies - McCarthy, Kevin Finbarr (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
Chronic pain involves a progressive disturbance of mood, sleep and physical function, with significant medical, social and economic consequences. The mechanism by which acute pain may become chronic and refractory to treatment is poorly understood. Interventional pain therapies such as radiofrequency (RF) treatment and spinal cord stimulation (SCS) are directed towards interrupting the afferent nociceptive input or modulating the upward transmission of these signals within the dorsal horn at the level of the spinal cord. These technologies are efficacious in select neuropathic pain syndromes and in denervating arthritic joints although their precise mechanism of action is unclear. Recent pre-clinical research has implicated glial activation and neuroinimune mediators in the pathophysiology of chronic pain.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin